Haematological parameters in single and twin pregnancies of sheep - Balikci, E; Yildiz, A (Indian Veterinary Journal, 2005)
There is paucity of information about the effects of single or twin pregnancy on the haematological parameters in sheep. Therefore a study was performed to follow the progress of haematological parameters at 60, 100 and 150 days of gestation and at 45 days postpartum in single and twin gestation of sheep.
Keywords: Profiles; Goats